Practicum tutorials in initial teacher training: conditions, strategies, and effects of reflective practice. Issue 1 (2nd January 2020) - Ruffinelli, Andrea; de la Hoz, Silvana; Álvarez, Carolina
ABSTRACT: This paper systematizes the research findings of publications in the last 5-years related to reflective practice in practicum tutorials in initial teacher training, by means of a literature review. The objective is to contribute new knowledge about reflective practice, structuring it around its conditions, development strategies, and effects, considering metacognitive and generative factors, enriching theory about how to teach reflection. The results show there is progress in the field in terms of proposals for different devices and strategies to teach reflective practice in initial teacher training, and emerging findings regarding its effects.